2023
DOI: 10.2337/db22-0639
|View full text |Cite
|
Sign up to set email alerts
|

The Antinarcolepsy Drug Modafinil Reverses Hypoglycemia Unawareness and Normalizes Glucose Sensing of Orexin Neurons in Male Mice

Abstract: Perifornical hypothalamus (PFH) orexin glucose-inhibited (GI) neurons that facilitate arousal have been implicated in hypoglycemia awareness. Mice lacking orexin exhibit narcolepsy and orexin mediates the effect of the anti-narcolepsy drug, modafinil. Thus, hypoglycemia awareness may require a certain level of arousal for awareness of the sympathetic symptoms of hypoglycemia (e.g., tremors, anxiety). Recurrent hypoglycemia (RH) causes hypoglycemia unawareness. We hypothesize that RH impairs the glucose sensiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Another possibility would be a role played in hypoglycemia awareness, a state of conscientiousness which includes a variety of symptoms (e.g., palpitations, anxiety, confusion) alerting for hypoglycemia and initiating behavioral responses to find energy. This is the case for lateral hypothalamus GI orexin neurons as it has recently been shown 44 . Other brain functions, including memory, motivation could be controlled, in addition to the CRR, by GSNs of these different neuronal networks.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Another possibility would be a role played in hypoglycemia awareness, a state of conscientiousness which includes a variety of symptoms (e.g., palpitations, anxiety, confusion) alerting for hypoglycemia and initiating behavioral responses to find energy. This is the case for lateral hypothalamus GI orexin neurons as it has recently been shown 44 . Other brain functions, including memory, motivation could be controlled, in addition to the CRR, by GSNs of these different neuronal networks.…”
Section: Discussionmentioning
confidence: 80%
“…This is the case for lateral hypothalamus GI orexin neurons as it has recently been shown. 44 Other brain functions, including memory, motivation could be controlled, in addition to the CRR, by GSNs of these different neuronal networks. Significant work is still needed to fully understand the functions controlled by these specific neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Since the activation of OX neurons is strongly associated with waking during an insulin induced hypoglycemia [ 53 ], this may have serious repercussions during nocturnal hypoglycemia, when timely arousal is necessary to rectify the falling BG levels, even when the epinephrine response is unaffected and precedes the awakening [ 54 ]. Indeed, a recent preclinical study demonstrated that OX neurons are a promising therapeutic target for restoration of hypoglycemia awareness in the recurrent hypoglycemia settings [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms by which modafinil exerts these effects are under study, with one study suggesting recurrent hypoglycemia impairs glucose sensitivity of perifornical hypothalamus (PFH) orexin glucose inhibited (GI) neurons which may play a role in development of IAH. In this rodent model, modafinil normalized glucose sensitivity to PFH orexin GI neurons post recurrent hypoglycemia with restoration of IAH ( Patel et al, 2023 ). In 2021, Espes et al published results from their proof-of-concept trial of six patients with T1D who were given a controlled release formulation of GABA, Remygen (Diamyd Medical) ( Espes et al, 2021 ).…”
Section: Pharmacological Interventions To Prevent or Reverse Impaired...mentioning
confidence: 93%